Nawawi al-Bantani, Ashhab al-Jawiyyin di Bidang Hadis: Rihlah, Genealogi Intelektual, dan Tradisi Sanad Hadis - Hafidhuddin Hafidhuddin; Saifuddin Zuhri Qudsy (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2021)
Nawawi al-Bantani as an archipelago scholar through the Tanqih al-Qaul has contributed to the study of hadith in the mid-nineteenth century AD. The intellectual tradition developed by Nawawi al-Bantani became the scientific traditions that developed in Haramayn (Mecca and Medina), and the traditions Islam in the archipelago, especially in Islamic boarding school on an ongoing basis. This study aims to determine the socio-historical intellectual traditions of Nawawi and fiqh al-hadith contained in the Tanqih al-Qaul. Departing from that, the historical research method is used in uncovering the object of research. The results of this study indicate that the Lubab al-Hadith by al-Suyuthi (d. 911) was first recited by Nawawi al-Bantani in the mid-nineteenth century AD, through the syarah compiled by Nawawi there were seven ideas in the context of understanding hadith (fiqh al-hadith), this refuses the notion that the study of the eyes has not been touched, Nawawi al-Bantani has made efforts in this regard. In addition, Nawawi as sayyid ulama’ al-hijaz and musnid, not only compiled hadith books and spread his thoughts in the field of hadith, which at that time was more oriented towards the dialectics of sufism and fiqih. Through Nawawi, the intellectual genealogy traditions called sanad continues to be continuous, especially for students and scholars in the archipelago after that and brings its own style to the tradition of learning hadith in Indonesia.